2017
DOI: 10.1007/s00586-017-5266-5
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of cannulated pedicle screw versus conventional pedicle screw for extra-pedicular screw placement in dysplastic pedicles without cancellous channel in adolescent idiopathic scoliosis: a computerized tomography (CT) analysis

Abstract: Usage of cannulated screw system significantly increases the accuracy of pedicle screw insertion in dysplastic pedicles in AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Different studies have proven that the use of cannulated screws in spinal surgery is an effective and reliable method [10,12,22,23]. In our study, we tried to increase our screw accuracy using cannulated iliac screws and compared them with the group in which we used classic iliac screws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have proven that the use of cannulated screws in spinal surgery is an effective and reliable method [10,12,22,23]. In our study, we tried to increase our screw accuracy using cannulated iliac screws and compared them with the group in which we used classic iliac screws.…”
Section: Discussionmentioning
confidence: 99%
“…We have not found any biomechanical studies on the stability of the iliac screws. Although the cannulated screws have been shown to be more fragile than conventional screws in a biomechanical study with pedicle screws [24], no weakness has been found in clinical studies [22,23]. To avoid any breakage problem while inserting a cannulated iliac screw, we sent the cannulated taper to the end and tried to bury it in the bone tissue with only the polyaxial part of the screw outside.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the misplacement of pedicle screws in AIS, extra-pedicle screws [20], PPSs, cannulate pedicle screws [8], intraoperative navigation, robot-assisted pedicle screws [21] and 3D-printing drill guide template [22] have been developed. Recently, some studies have reported the clinical use of cannulated pedicle screws.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, since the vertebra becomes more concave in the upper thoracic region, misplacements may occur even though the path of the screw is prepared by tapping when the extrapedicular screw is sent. [4,6] Moreover, as the screw heads are much wider than the screw, the transverse process may turn the direction of the screw towards the lateral area when the screw heads contact with the transverse processes while the screw is advanced. However, in the presence of a guidewire, this wire will assure the direction of the screw.…”
Section: Discussionmentioning
confidence: 99%
“…Cannulated pedicle screws (CPSs) are increasingly preferred by many spinal surgeons to increase the accuracy of the screws. [ 5 , 6 ]…”
Section: Introductionmentioning
confidence: 99%